Cárdenas e Jesuítas na província do Paraguai do século XVII : disputa e sobreposição de poderes - Dalcin, Éverton (2015)
The present investigation aims at analysing the alliance between the State and the Church according to the actions of Ordem de São Francisco and Companhia de Jesus, at Rio da Prata Colonial territory. The analysis will be carried out from the conflict involving the jesuits and the Franciscan Bernardino de Cádenas, nominated Bishop of Assunção in 1638 and Governor in 1649, thus gathering both the religious and the civil power of the Province in his hands. The time ranging between the two nominations corresponds to the period of the conflict which starts at the arrival of the new Bishop to Paraguay, in 1642 and will continue up to1660, when the courts of Rome and Spain will decide on the conflict. The feud breaks out due to the economic crisis in Paraguai, as the local settlers could not find satisfactory native labor to help them. Their difficulties continued increasing, mainly after the jesuits stablished the Jesuitic reductions according to which the reduced natives could not be incorporated to the encomienda system. This study will also indicate some differences and similarities in the reduction model proposed by the religious Orders, as well as their relations with the Royal Patronage, which will start to provide the jesuits with privileges, originating an overlap of powers which will generate the conflict.